Kokami Game Effectivity within 5th Grader Students' Aptitude Improvement of Arabic Writing at Chariyattham Wittaya Narathiwat Secondary School Southern Thailand - Mafajah Salsabila Alfarisi; Khizanatul Hikmah (Universitas Muhammadiyah Sidoarjo, 2022)
This study based on the condition of Muslim students in Southern Thailand that was difficult to understand Arabic language. Researchers are triggered to know how to implement and how effective Mysterious Box and Card Game (known as KOKAMI) in improving Arabic writing skill towards 5th grade students at the Chariyattham Wittaya Narathiwat School in Southern Thailand. This study is designed to be quantitative with pre-experimental design in the form of one group pre-test and post-test. Data are collected through observation, interview, documentation and test. Further, data are analysed using t-test formula. The results showed that KOKAMI game has effectively enhanced Arabic writing skill of the 5th grade students at the Chariyattham Wittaya Narathiwat School in Southern Thailand with a ratio of tcount 8,881> ttable 2,201. This means H1 is accepted.